Name ___________________________________________
© 2006 A2   www.mathnstuff.com/papers/condots/trisub1a.htm
Trinomial Subtraction

Connect the dot for an answer to the dot for the previous answer.
Simplify each expression.
1.)   (5x2 - 2x + 3) - ( x2 + 4x + 2)= 4x2 - 6x + 1
2.)   (6x2 - 3x + 4) - (4x2 + x + 5)= 2x2 - 4x - 1
3.)   (7x2 + 4x + 1) - (4x2 + 2x + 2)=3x2 + 2x - 1
4.)   (12x2 + 12x) - (12x2 + 7x)=5x
5.)   (6 + 4x - 5x2) - ( 4 + 4x - 8x2)=3x2 + 2
6.)   (12x2 - 4x + 5) - (12x2 - 13x + 3)=9x + 2
7.)   (-9x2 + 5x -4) - (-13x2 - 10)=4x2 + 5x + 6
8.)   (2x2 + 5x) - (-x2 + 3x - 1)=3x2 + 2x + 1
9.)   (5x2 + 7x - 1) - ( 5x2 + 4x + 1)= 3x - 2
10.)   (3x2 - 5x + 5) - (x2 - 2x + 1)= 2x2 - 3x + 4
11.)   (6x2 + 5x + 2) - (6x2 - 4x + 1)= 9x + 1
12.)   (2x2 + 4x + 1) - ( -x2 + 4x - 1)=3x2 + 2
Start a new line.
13.)   (x2 - 3x + 2) - ( -3x2 + 3x + 1)=4x2 - 6x + 1
14.)   (-6x2 + 3x - 4) - ( -6x2 - 2x - 2)= 5x - 2
15.)   (17x2 + 5x) - ( 16x2 + 7x)= x2 - 2x
16.)   (-3 + 4x + 9x2) - ( - 4 -5x + 9x2)= 9x + 1
Start a new line.
17.)   (12x2 + 4x + 2) - ( 7x2 - 3x + 5)= 5x2 + 7x -3
18.)   (2x3 + 5x2 - 6x + 3) - ( 5x2 - 12x + 3)= 2x3 + 6x
19.)   (-2x2 - 6x + 1) - ( 2x2)= - 4x2 - 6x + 1
20.)   (8 + 6x + 5x2) - ( 11 + x + 5x2)= 5x - 3
21.)   (2x2 + 8x + 6) - ( 2x2 + 10x + 6)= -2x
22.)   (x2 - 3x + 5) - ( -2x2 + 2x + 1)=3x2 - 5x + 4
23.)   (5x2 + 7x + 2) - ( 5x2 + 7x - 2)= 4
24.)   (10x2 - 3x + 2) - ( 5x2 + 6x + 3)= 5x2 - 9x - 1
25.)   (15x2 + 5x - 2) - ( 12x2 + 5x - 2)= 3x2
26.)   (6x2 + 8x + 5) - (6x2 + 4x + 5)= 4x